(untitled) (LACCEI, 2024)
The objective of this research was to evaluate the acceptability of canned Anchovy in quinoa sauce (Chenopodium quinoa Willd) and Kiwicha (Amaranthus caudatus L.) as the governing liquid. The research was of the experimental type and a unifactorial design was applied. A sauce was prepared with carrot (17%), celery (7%), leek (9%), onion (4%), potato (9%), oregano (1%), salt (2), parsley (3%) and water (50%). To formulate the governing liquid, 60% of the base sauce and 40% of precooked kiwicha or quinoa grains were used. A sensory evaluation was carried out by means of the Paired Comparison preference test to 42 panelists, with greater preference for the preserves with quinoa sauce. The ideal profile based on CATA questions was evaluated for both products, finding significant differences (95% reliability) in two descriptors used. The sensory attributes essential for acceptability for canned fish with quinoa sauce and canned fish with quinoa sauce were: semi-soft fish flesh and very dark fish flesh. It is concluded that canned anchoveta in kiwicha sauce and quinoa sauce is a product with a good nutritional contribution, but the product and/or process should be improved based on the results of the CATA analysis.